Fraudulent Financial Reporting: How far has it been Researched? - Puspita, Amelia Tri; Taqi, Muhamad (SMART Insight, 2023)
This study aims to determine the development and trend map of fraudulent financial reporting research that is published by a reputable journal in the theme of economics and finance. The data analyzed were more than 91 publications of indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to find out the bibliometric map of the development of the research in this topic. The results showed that the number of publications on the fraudulent financial reporting research experienced a significant increase. The results show that the most popular authors are Groove H and Carcello JV, and the most popular keyword topics are Financial, Reporting, and Fraudulent. Apart from that, there are several trend topics related to fraudulent financial reporting.